Uncovering the dimensions of public value in public procurement: a systematic literature review - Oliveira, N.; Martins, A. (Euroma 2025, 2025)
Public procurement is still loaded with challenges that involve a constant management of trade-offs, nevertheless, it can generate broader outcomes for all stakeholders. This systematic literature review investigates the integration of public value theories in public procurement processes, exploring a value-oriented approach that maximizes procurement outcomes. The research synthesizes diverse perspectives on public values within procurement, emphasizing the complexities of stakeholder interactions and the need for co-creation engagement. Procurement is moving from a traditional focus on cost minimization to embracing value multi-dimensional perspective. By analysing peer-reviewed articles, this review provides insights that leverage public procurement process, ultimately advocating for a strategic shift into a public values perspective.